Revisión de las principales reducciones del impuesto a la renta y su incidencia en la conciliación tributaria en Ciguemotors Rectificadora en el período 2018. - Catucuamba Asimbaya, Nathaly Vanessa (2020)
This research project is based on what is stipulated in the Internal Tax Regime Law (LORTI), constituting a guide for tax reconciliation with the correct application of deductible expenses, covering certain fundamental aspects, such as duly justified exemptions and deductions by the taxpayer, determining and establishing effects that its application produces in the tax conciliation on certain commercial activity, considered as a component the taxpayer's total income. The main problem of the Ciguemotors microenterprise dedicated to providing repair and rectification services for engine parts, seats, compression check, cleaning, brushing of diesel and gasoline vehicles, ignore tax updates, hindering the information they generate for calculation of income tax, resulting in excessive or low payment thereof. For this reason, the research purpose is focused on analyzing the incidence on income tax deductions in the tax reconciliation, by applying the tax regulations in force in Ciguemotors, specifically in the 2018 period. Using the mixed research approach ( quantitative and qualitative); Through the bibliographic and field documentary methodology, through the techniques of the interview and direct observation, using instruments such as the interview and observation sheet, the information needed to achieve the project was collected. It is concluded that when applying the deductible expenses, the value of the income tax to be paid, is greater than that determined by the microenterprise, due to ignorance of the legal provisions, that is, they record all expenses as deductibles without considering those established in the regulations such as travel expenses, management, advertising, remuneration and fixed assets, obtaining a representative difference of $ 5,492.74 through the review, calculation and analysis of the documentation that justifies the economic movements of the 2018 period.